THE EFFECT OF MIND MAP NOTING TECHNIQUE TOWARDS STUDENTS` CONCEPT MASTERY - Nani Nani; Pramudiyanti Pramudiyanti; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
The Biology learning process  in the  eight grade class of Junior High School  IX Bandar Lampung  is dominated by the teacher whose uses lecuring teaching strategis. This situation needs students to note the information fast and  properly. The purpose of this study was to determine the effect of using mind map noting technique to improve students' biotechnology concepts mastery and students' learning activities. Students of class IXE and  class IXC was chosen  as sample using  randomize block design sampling technique. The study used pre-post test non equivalent design, and obtained of the quantitative data using   and N-gain score.The qualitative data were aspects of students` learning activities. Quantitative data were analyzed using SPSS 17 software while the qualitative data were analyzed descriptively.The results showed that the effect of mind map noting technique  had not significantly improved the students`s concepts mastery. However the students` activities  increased  as much as  23.06%. Thus, the use of mind map noting techniques can influence students` learning activities and students` mastery of biotechnology concepts. Keywords: mind map, activity, concept, biotechnology.